Histological Findings in Portal Gastropathy and Its Association with Child-Pugh Score in Liver Cirrhosis - Aftab Abbasi, Musarat Kalhoro, Mehtab Abbas! (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2016)
Objective: To investigate histological findings of portal gastropathy (PG) and its association to Child Pugh score in liver cirrhosis. Methods: Eighty five diagnosed cases of liver cirrhosis were selected for this cross sectional study, conducted in the department of Anatomy and Medicine/Isra University Hyderabad from June to December 2012. Sampling used was non-probability convenient and followed inclusion and exclusion criteria. Olympus XQ 140 (version 3) endoscope was used to obtain 2 mm thick tissue specimen by punch biopsy. Biopsy sample was washed with 0.9% NaC1 followed by fixing into 10% formaldehyde. Portal Gastropathy (PG) was graded as none, mild, moderate, and severe on hi stopatho logy, SPSS 21.0 version was used for the statistical analysis (p-value of? 0.05). Results: Mild, moderate, severe and no gastropathy were observed in 52.9%, 34.1%, 4.7%, and 8.2% respectively. An increase in gastric glands was observed. Pyloric antrum showed lamina propria infiltrated with inflammatory cells in most of tissue samples. Similarly gastric mucosa thickness as mild, moderate and severe was noted in 11.8%, 8.2% and 6.4% of cases respectively. Capillary dilatation and edema of lamina propria was noted in 9.4% of cases, rest revealed no such observation. Portal gastropathy (PG) and Child Pugh Class (CPC) association showed a positive correlation of r=0.674 (p-0.011). Conclusion: Stomach revealed changes in gastric mucosa and its thickness, gland size and number and presence of inflammatory infiltrate parallel to severity of Child Pugh score.